Autoestilismo em diáspora: modelando tradições têxteis desde o Hip-hop - Corrêa, Jaergenton de Souza (2014)
This research presents the developments of the textile family production, as support for the cultural preservation and the strengthening of african diasporic traditions in Brazil. From the contact with HIP-HOP, artistic, political, cultural and educational mediations are established through the tissues. New technologies and influences with various inhabited diasporas in São Paulo provided the adaptation of the textile tradition in order to gain personal and collective autonomy, where each body is the proponent of its expansion, by personal and ancestral experience transposed in modelling and stamping. The meeting between sports, the peripheral landscape and the virtual world resulted in disconnected performing propositions for the rails of the classic Eurocentric fashion catwalk, which will be analysed here as resistance from the oral tradition shaped in clothing